Three Proverbial Triads: Sapiential Imperatives for a Peaceful Existence - Mieder, Wolfgang (Tautosakos darbai, 2026)
The number three has played a major role in cultural, folkloric, and linguistic tradition. There are numerous proverbs based on a triadic structure in various languages dating back to antiquity and continuing to this day. But there are also so-called proverbial triads consisting of but a string of three words like “Veni, vidi, vici”, “Wein, Weib und Gesang”, “Liberté, égalité, fraternité”, and “Blood, sweat, and tears”. Many folk triads like “Ready, willing, and able” and “Signed, sealed, and delivered” also abound. Of special interest are three American triads based on the fundamental ideas of a free and democratic society, namely “Life, liberty, and the pursuit of happiness”, “Government of the people, by the people, and for the people”, and the less well known and newer “Freedom, justice, and democracy”. The origin, history, dissemination, and meaning of these formulaic triads are discussed in considerable detail with contextualised references. They express the belief in and call for a democratic world based on peaceful, fair, and humane coexistence. Of course, these fundamental proverbial triads also show that there exists a natural inclination to state basic socio-political principles in an easy to remember triadic pattern.